2022
DOI: 10.1038/s41467-022-33615-z
|View full text |Cite
|
Sign up to set email alerts
|

Uniformly aligned flexible magnetic films from bacterial nanocelluloses for fast actuating optical materials

Abstract: Naturally derived biopolymers have attracted great interest to construct photonic materials with multi-scale ordering, adaptive birefringence, chiral organization, actuation and robustness. Nevertheless, traditional processing commonly results in non-uniform organization across large-scale areas. Here, we report magnetically steerable uniform biophotonic organization of cellulose nanocrystals decorated with superparamagnetic nanoparticles with strong magnetic susceptibility, enabling transformation from helico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 71 publications
1
32
0
Order By: Relevance
“…From the X-ray diffraction (XRD) spectrum (Figure S6), with the increase SSWPU content, the crystallinity of the composite film decreased. While all the characteristic peaks of CNC were retained, corresponding to the (101), (101̅ ), (002), and (040) lattice planes of cellulose I, 41,42 it indicated that the introduction of the SSWPU would not affect the crystalline structure of CNC films. The FPFS and SSWPU were also characterized by attenuated total-reflection Fourier transform infrared (ATR-FTIR), and there was no absorption band appearing at 2270 cm −1 , which indicated that the −NCO group in the system had completely reacted.…”
Section: Resultsmentioning
confidence: 97%
“…From the X-ray diffraction (XRD) spectrum (Figure S6), with the increase SSWPU content, the crystallinity of the composite film decreased. While all the characteristic peaks of CNC were retained, corresponding to the (101), (101̅ ), (002), and (040) lattice planes of cellulose I, 41,42 it indicated that the introduction of the SSWPU would not affect the crystalline structure of CNC films. The FPFS and SSWPU were also characterized by attenuated total-reflection Fourier transform infrared (ATR-FTIR), and there was no absorption band appearing at 2270 cm −1 , which indicated that the −NCO group in the system had completely reacted.…”
Section: Resultsmentioning
confidence: 97%
“…On the other hand, the addition of electrolytes decreased the zeta potential due to the shielding of the EDL, as a result, the zeta potential of CHWs suspensions declined with the increase of the ionic strength as presented in Figure e . Concerning the degree of ordering of the whiskers assembly, AFM was also used to further deeply investigate the surface topology of the dry films of CHWs suspensions treated with various ionic strengths, as presented in Figure d. , Obviously, the microscopic arrangement structure of CHWs showed better order at low ionic strength, and the CHWs became disordered and disorganized with increasing ionic strength, even leading to severe agglomeration, that is, it demonstrated the effect of ionic strengths on the assembly of CHWs as a result of the ordering of CHWs from highly oriented to randomly oriented, which was consistent with the phenomenon observed by TEM …”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al [ 29 ] obtained a lighter, more translucent colour due to the acid hydrolysis treatment used to obtain BC nanocrystals before doping with a low concentration of up to 12% in mass of magnetite. With these methods, the authors sought to align the spatial orientations of magnetic BC nanocrystals, leaving the material translucent and ideal for photonic applications.…”
Section: Magnetic Bacterial Cellulose Biopolymersmentioning
confidence: 99%
“…Another common form of incorporation is the addition of ready-made magnetic compounds synthesized ex situ, which is described in several works [ 29 , 81 , 86 , 87 , 94 ]. For instance, Sriplai et al [ 87 ] incorporated magnetite in BC in a very simple way.…”
Section: Magnetic Bacterial Cellulose Biopolymersmentioning
confidence: 99%
See 1 more Smart Citation